2016
DOI: 10.1002/asjc.1320
|View full text |Cite
|
Sign up to set email alerts
|

Exponential Stability Analysis for Stochastic Delayed Differential Systems with Impulsive Effects: Average Impulsive Interval Approach

Abstract: This paper is concerned with the exponential stability analysis of stochastic delayed systems with impulsive effects. By using the average impulsive interval approach, and together with comparison lemma and Razumikhin techniques, sufficient conditions ensuring the moment exponential stability of the systems under consideration are established. A stability criterion for non‐delayed stochastic systems with impulses is also derived as a corollary. Compared with the existing stability results in the literature, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…In this paper, the problem of exponential lag synchronization of memristive neural networks with reaction diffusion terms via neural activation function control has been firstly investigated. Compared with the results in [17][18][19][20], the results obtained in this paper are more general and more practicable.…”
Section: Remarkmentioning
confidence: 56%
See 1 more Smart Citation
“…In this paper, the problem of exponential lag synchronization of memristive neural networks with reaction diffusion terms via neural activation function control has been firstly investigated. Compared with the results in [17][18][19][20], the results obtained in this paper are more general and more practicable.…”
Section: Remarkmentioning
confidence: 56%
“…In practical applications, reaction diffusion effect cannot be avoided in the neural network models when electrons are moved by voltage in asymmetric electromagnetic fields, the activation functions and the states of system not only depend on time, but also intensively depend on space in many circumstances. In [17][18][19][20], the stability and synchronization of neural networks with reaction diffusion terms have been considered, it is very important to consider the state of memristive neural network systems varying in space as well as in time. is the state of the ith subsystem, f i and g i is the amplifier, R i is the connection resistors between the amplifier f i ∕g i and state y i (.…”
Section: Introductionmentioning
confidence: 99%
“…sive stabilization of impulsive stochastic functional differential systems, including impulsive stochastic delay systems, have received a large number of research interests and many results have been reported (see, e.g. [19][20][21][22][23][24]). Specifically, by using Lyapunov functions, some Razumikhin-type theorem on the exponential stability of impulsive stochastic functional differential systems were established in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, impulsive effects may exist widely in many evolutionary processes in which they experienced changes of state abruptly at certain moments in the fields such as economics, medicine, and biology (see, e.g., [11][12][13][14][15][16][17][18]). More recently, some results on impulsive stochastic functional equations with Markovian switching have been reported in [19][20][21][22][23][24][25] .…”
Section: Introductionmentioning
confidence: 99%